(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This research was conducted to assess the influence of CSN2 exon 7 milk production and the additive and dominance effects. Materials and Methods: DNA was isolated from 64 goats that possessed the CSN2 gene and subjected to a polymerase chain reaction and genotyping by Sanger sequencing. Genotype effect can be assessed through analysis of variance and the generalized linear model, which can estimate additive and dominance effects. Results: Dairy traits are greatly influenced by the crucial role played by the CSN2 gene. The influence of SNP g.8946C > T on milk yield (MY) is statistically significant (p < 0.05). Nevertheless, the impact of SNP g.8956G > A on MY is not statistically significant. Furthermore, the MY of Sapera goats is affected by both Parity (p < 0.01) and days in milk (p < 0.01). Conclusion: The CC genotype demonstrates a higher MY without noticeable additive or dominance effects. Evaluating the SNP g.8946C > T necessitates many samples and phenotypes. J. Adv. Vet. Anim. Res., 12(4): 1211–1216, December 2025 http://doi.org/10.5455/javar.2025.l981